Structural Transition Dynamics in Carbon Electrode‐Based Single‐Molecule Junctions. Issue 2 (27th January 2021) - Li, Peihui; Jia, Chuancheng; Guo, Xuefeng
Abstract : A reliable strategy of using single‐molecule electrical approaches to study molecular structure transitions at the single‐molecule level in real time was introduced. Abstract: Monitoring the structural transitions of individual molecules is of great significance because it helps to in depth explore the properties of molecules and provide diverse possibilities for molecular applications in the fields of chemistry, biology and material science. This review summarizes the strategy of using single‐molecule electrical approaches to study molecular structure transitions at the single‐molecule level in real time. Specifically, through the use of stable single‐molecule devices for real‐time electrical monitoring, the process of molecular structure transitions of a single molecule can be investigated, which helps to explore the nature of molecules in chemical and biological systems. In particular, the detection methods have been extended to the investigation of biological macromolecules for monitoring the conformational changes of nucleotide chains in different systems, such as double helix DNA, aptamer and DNA enzyme. In the end, we discuss the future challenges of probing structural transitions of single molecules, and provide prospects for further breakthroughs in this field. What is the most favorite and original chemistry developed in your research group? Single‐molecule device fabrication and detection. How do you get into this specific field? Could you please share some experiences with our readers? I started to pursue this field during my PhD period. The promise of molecular electronics that might breakthrough the development bottleneck of current microelectronics inspired my great interest. This interest drives me to persist in the pursuit of practical molecular electronic devices as perfect as possible. What is the most important personality for scientific research? Three aspects: interest, persistence and industriousness. The first key to the success should be diligence. How do you keep balance between research and family? It is hard to balance the time. It is very important to have understanding and support from the family. I love them. What's your hobbies? Driving and watching movies.